Rome: a very special, extraordinary, very weak, very difficult normal city (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Rome is an inadequate city of a modern, small and relatively recent central state, which, however, has found the national foundation on the myths of the city to affirm politically the unitary values that poetry and art had brought out as possible and shared . But Rome, as guardian of supranational myths, is itself two-faced. To fully understand the nature of the modern city grown in Rome in the last one hundred and fifty years, we could compare, for once, the rise of the modern nation called Italy, to the formation of modern South American nations, rather than to the realization of the main historical nations of Europe.